Construction Tradespeople Perception of the Factors Motivating Labour Productivity on Construction Projects - Eze, Emmanuel Chididebere; Nwaki, William Nkeonyeasua; Obonadhuze, Bernard Inibuh (Journal of Technology Management and Business, 2020)
Construction productivity defines the wealth of a nation as well as the well-being of its citizenry, because it plays a critical role in the overall economic development of a nation. However, there has been a reported decline in labour productivity which has led to poor delivery of construction projects. This issue has been among the leading causes of schedule and cost overruns, quality issues, claims and conflicts, especially in key capital construction projects globally. Poor labour productivity is attributed to the reaction of workers on certain factors.  The purpose of this study is to assess construction tradespeople perception of the factors motivating labour productivity on construction projects. To achieve this purpose, semi-structured interview and questionnaire, and a stratified purposeful sampling technique was adopted to gather data from construction tradespeople in Port Harcourt, Nigeria. Data gathered through survey from 106 construction tradespeople, were analysed using frequencies, percentage and factor analysis. The data gathered from 25 interviewees were analysed using thematic analysis. The study concluded that major factors motivating construction tradespeople productivity on construction projects are knowledge and salary-related factors; job security and planning related factors; health, safety and promotion related factor; overtime and work area condition; team building and equipment factors; supervision and recognition factors; management and teamwork factors; and materials and work methods. Furthermore, the implication of the role of financial and non-financial motivators is brought to the fore in ensuring improved and sustainable labour productivity on construction projects. The study recommended that construction organisations should utilise a good mix of financial and non-financial productivity motivators in getting the best out of their employees, especially the site operatives.